Matematyka

Autorzy:Adam Makowski, Tomasz Masłowski, Anna Toruńska

Wydawnictwo:WSiP

Rok wydania:2015

Wyrażenie (2x-3)(4x-3)-(2x-3)(3x-1) można zapisać w postaci 4.6 gwiazdek na podstawie 10 opinii
  1. Gimnazjum
  2. 1 Klasa
  3. Matematyka

Wyrażenie (2x-3)(4x-3)-(2x-3)(3x-1) można zapisać w postaci

1
 Zadanie

2
 Zadanie

3
 Zadanie
4
 Zadanie
5
 Zadanie

`(2x-3)(4x-3)=2x(4x-3)-3(4x-3)=8x^2-6x-12x+9=8x^2-18x+9` 

 

`(2x-3)(3x-1)=2x(3x-1)-3(3x-1)=6x^2-2x-9x+3=6x^2-11x+3` 

 

`(2x-3)(4x-3)-(2x-3)(3x-1)=(8x^2-18x+9)-(6x^2-11x+3)=` 

`=ul(8x^2)-ul(ul(18x))+ul(ul(ul9))-ul(6x^2)+ul(ul(11x))-ul(ul(ul3))=2x^2-7x+6\ \ \ \ odp.\ D`